Effects of growth stimulating implants and implanting sequence on steer performance - Fink, G.; Riley, Jack G. (Kansas State University. Agricultural Experiment Station, 2011)
Three trails used 264 steers to evaluate the effects of 36 mg zeranol (Ralgro) and 20 mg estradiol benzoate plus 200 mg progresterone (Synovex-S) implants on performance of steers during one growing and two finishing studies. Daily gain during the 105-day growth trial by steers implanted with Ralgro ®. Before a 151-day finishing trial, equal numbers from each implant group in the growth trial were re-implanted with either R or S so we had four implanting sequences each of two implants: SS; SR; RS; and RR. Implant sequences SR, RS, and RR all gave similar performances and produced faster (P<.05) gains than implant sequence SS. Combining the growing and finishing phases into a 256-day implanting program resulted in no significant differences in daily gain by implant sequence. In a second finishing trial, we compared a single implant of S or R in a 108-day trial. Rate of gain did not differ significantly. Also, carcass measurements did not differ significantly by implant.
Keywords: Beef; Implants; Steers; Performance